Mental Health and the Timing of Men's Retirement - Gill, S.C.; Rodgers, B; Anstey, K.J.; Butterworth, P (My University, 2006)
Background Analysis of the Psychiatric Morbidity Survey of Great Britain showed that the prevalence of common mental disorders was lower amongst men at or above Britain’s state pension age of 65, relative to younger men. Retirees below this age had consistently higher rates of mental disorders than working men. In contrast, the low prevalence of mental disorders amongst retirees aged 65 and older was similar to that of their working peers. The aim of this analysis was to investigate this pattern of results in a national sample of Australian men, and the mediating role of socio-demographic factors. Method Data were from the Household, Income and Labour Dynamics (HILDA) in Australia survey (2003). The analyses included men aged 45–74 years who were active in the labour force (n = 1309), or retired (n = 635). Mental health was assessed using the mental health scale from the Short-Form 36 Health Questionnaire. Results Retirees were more likely to have mental health problems than their working peers, however this difference was progressively smaller across age groups. For retirees above, though not below, the age of 55 this difference was explained by poorer physical functioning. When age at retirement was considered it was found that early retirees who were now at or approaching the conventional retirement age did not display the substantially elevated rates of mental health problems seen in their younger counterparts. Further, men who had retired at age 60 or older did not display an initially elevated rate of mental health problems. Conclusions The association between retirement and mental health varies across older adulthood. Retired British and Australian men below the conventional retirement age of 65 are more likely to have mental health problems relative to their working peers, and retirees above this age. However, poor mental health appears to be linked to being retired below this age rather than an enduring characteristic of those who retire early.
Social Psychiatry and Psychiatric Epidemiology
Keywords: Health -- Mental; Ageing -- Retirement; Ageing; Gender; Gender -- Male; Health; Ageing; Gender; Health and wellbeing; Ageing; Health; Gender; Retirement; Mental; Male; Health and wellbeing; Ageing; Gender